Do Market Pressures Induce Economic Efficiency? The Case of Slovenian Manufacturing, 1994-2001 - Orazem, Peter F.; Vodopivec, Milan (Washington, DC: World Bank, 2013)
The Slovenian transition represents a slow, but steady liberalization of constraints on competition. Using a unique longitudinal data set on all manufacturing firms in Slovenia over the period 1994-2001, the authors analyze how firm efficiency changed, in response to changing competitive pressures, holding constant firm attributes. Results show that the period was one of atypically rapid growth of total factor productivity (TFP), relative to levels in OECD countries, and that the rise in firm efficiency occurs across almost all industries and firm types - large or small, state or private, and domestic or foreign-owned. Changes in firm ownership type, have no impact on firm efficiency. Rather, competitive pressures that sort out inefficient firms of all types, and retain the most efficient, coupled with the entry of new private firms that are at least as efficient as surviving firms, prove to be the major source of TFP gains. Market competition from new entrants, foreign-owned firms, and international trade, also raise firm efficiency in the industry. Results strongly confirm that market competition fosters efficiency.